Correction: Spanish version of the short European Health Literacy Survey Questionnaire HLS-Q12: Transcultural adaptation and psychometric properties. - Sergio Muñoz-Villaverde; Leticia Serrano-Oviedo; María Martínez-García; Yolanda Pardo; Llüisa Tares-Montserrat; Francisco Javier Gómez-Romero; Paloma Garcimartin (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0299736.].